1952
DOI: 10.1139/v52-099
|View full text |Cite
|
Sign up to set email alerts
|

A Spectroscopic Study of Hydrogen Bonding in Performic and Peracetic Acids

Abstract: The infrared spectra of concentrated performic and peracctic acids were measured in the rock-salt region. The most significant features are theO-Hstretching frequency a t 3310-3350 cm.-1 and the O H bending frequency a t 1450 cm.-1 which, for both peracids, remain essentially the same in the vapor state a s in the liquid or in solution in nonpolar solvents. This is attributed to i~~tramolecular hydrogen bonds resulting in particularly stable five-membered rings, 0 .Steric conditions in the percarboxylic group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

1964
1964
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 12 publications
(17 reference statements)
6
17
0
Order By: Relevance
“…From two X-ray studies [2] [3] it appears that, in the crystalline state, two peroxycarboxylic acid molecules are held together by H-bonds. An earlier microwave investigation of peroxyacetic acid revealed that the conformation in the gaseous state is strongly influenced by an intramolecular H-bond [4].This observation is in accord with recent ab initio calculations [5] and the fact that peroxycarboxylic acids do not dimerize in the gaseous state unlike carboxylic acids [6]. With the exception of a deuteriated species [4], we know of no reports of the preparation of isotopically substituted species of peroxycarboxylic acids.…”
supporting
confidence: 72%
“…From two X-ray studies [2] [3] it appears that, in the crystalline state, two peroxycarboxylic acid molecules are held together by H-bonds. An earlier microwave investigation of peroxyacetic acid revealed that the conformation in the gaseous state is strongly influenced by an intramolecular H-bond [4].This observation is in accord with recent ab initio calculations [5] and the fact that peroxycarboxylic acids do not dimerize in the gaseous state unlike carboxylic acids [6]. With the exception of a deuteriated species [4], we know of no reports of the preparation of isotopically substituted species of peroxycarboxylic acids.…”
supporting
confidence: 72%
“…Molecular orbital calculations generally predict two minima for the rotation about the N -O bond in hydroxylamines, and favour the trans confor mation by about 3 kJ/mol in energy [4c, d]. How ever, in some cases IR studies of H2NOH and its methyl derivatives give contadictary results as far as the conform ation is concerned [14].…”
Section: Bond Lengths [A]mentioning
confidence: 99%
“…This relationship even holds for the case of the percarboxylic acids (7,15). In fact the correlation is a fairly close one; but this must be fortuitous as the other OH force constants also are involved here.…”
Section: mentioning
confidence: 59%